Intermolecular CH Bond Activation by a Cationic Iridium(III) Dichloride Phenanthroline Complex1. (13th April 2015) - Swift, Christopher A.; Gronert, Scott
Abstract It is demonstrated that a cationic iridium(III) dichloride phenanthroline complex is capable of CH activation and H/D exchange. It can cleave benzylic and unactivated secondary CH bonds, but exhibits unique selectivity when compared to similar systems that have been studied in the condensed phase. Gas‐phase rate constants and kinetic isotope effects are reported for a variety of substrates and the analysis is supported by DFT calculations at the M06/QZVP level.